Mechanization and efficiency in rice production in China - Min SHI; Krishna P. PAUDEL; Feng-bo CHEN (Journal of Integrative Agriculture, 2021)
Agricultural mechanization and custom machine services have developed rapidly in China, which can influence rice production efficiency in the future. We calculate technical efficiency, allocative efficiency, and scale efficiency using data collected in 2015 from a face-to-face interview survey of 450 households that cultivated 3096 plots located in the five major rice-producing provinces of China. We use a one-step stochastic frontier model to calculate technical efficiency and regress the efficiency scores on socio-demographic and physical land characteristics to find the influencing variables. Variables influencing technical efficiency are compared at three different phases of rice cultivation. We also calculate technical efficiency by using the Heckman Selection Model, which addresses technological heterogeneity and self-selection bias. Results indicate that: (1) the average value of technical efficiency using a one-step stochastic frontier model was found to be 0.74. When self-selection bias is accounted for using the Heckman Selection Model, the average value of the technical efficiency increases to 0.80; (2) mechanization at the chemical application phase has a positive effect on technical efficiency, but mechanization does not affect efficiency at the plowing and harvesting phases; (3) machines are overused relative to both land and labor, and high machine input use on the small size of landholding has resulted in allocative inefficiency; (4) rice farmers are overwhelmingly operating at a sub-optimal scale. Future policies should focus on encouraging farmland transfer in rural areas to achieve scale efficiency and allocative efficiency while promoting mechanization at the chemical application phase of rice cultivation to improve technical efficiency.